Analisi Laju Aliran Massa Minyak Jelantah Dan Evaluasi Efisiensi Ekonomi Pada Kompor UMKM Kerupuk - Wahyu Abdillah; Syamsul Bahri Widodo; Fazri Amir (JURUTERA - Jurnal Umum Teknik Terapan, 2026)
Waste cooking oil has considerable potential as an alternative fuel for small-scale food industries, particularly for reducing waste and supporting sustainable energy utilization. However, information regarding the mass flow characteristics of waste cooking oil burners for MSME applications remains limited. This study aims to analyze the mass flow rate of a waste cooking oil burner designed for cracker production and evaluate its operational feasibility based on fuel consumption and operating cost. The experimental system consisted of a self-designed dual-burner stove equipped with flow meter sensors, anemometers, and an Arduino-based data acquisition system. The results showed that the mass flow rates of burner 1 and burner 2 were 0.00691 kg/s and 0.00520 kg/s, respectively, with an air velocity of 4.2 m/s for both burners. Operational testing indicated that approximately 0.480 L of waste cooking oil was consumed to fry 1 kg of crackers. Economic evaluation revealed that although waste cooking oil required higher operational costs than firewood under the investigated conditions, its availability from production waste offers potential as an alternative fuel for MSME applications. These findings provide useful baseline information for the design and optimization of waste cooking oil burner systems in small-scale food processing industries.